Case Report: Malignant Brain Tumors in Siblings With MSH6 Mutations - Wu, Di; Chen, Qingshan; Chen, Jian (Frontiers in Oncology, 2022)
Background: Familial brain tumor incidences are low. Identifying the genetic alterations of familial brain tumors can help better understand the pathogenesis and make therapy regimens for these tumors. Case presentation: An elder female and a younger male were diagnosed with brain tumors at the age of 10 and 5, respectively. Whole-genome sequencing analysis of the two patients’ blood, primary brain tumor tissues, and their parents’ blood samples was performed, which revealed that the two tumor samples harbored extremely high somatic mutation loads. Additionally, we observed pigmentation on the male patient’s skin. Conclusion: Germline, biallelic mutation of MSH6—a gene related to DNA mismatch repair whose defect will result in Constitutional mismatch repair deficiency (CMMRD)—is causal for the brain tumors of these two siblings.